2013
DOI: 10.4161/chan.22737
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular P2X receptors as novel calcium release channels and modulators of osmoregulation inDictyostelium

Abstract: Addendum to: Sivaramakrishnan V, Fountain SJ. A mechanism of intracellular P2X receptor activation. J Biol Chem 2012; 287:28315-26 However, later studies refuted a functional role of intracellular P2X receptors in Dictyostelium. Here we provide evidence that the discrepancies reported between the studies are due to the laboratory strain of Dictyostelium employed, which display different phenotypes in response to hypotonic stress and a varied dependency upon P2X receptors for osmoregulation. We use the recent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…This result is in accord with the basic function of P2X receptors as ligand-gated ion channels which open to allow ions such as Na+, Ca2+ to pass through the membrane [14]. However, 28 out of 180 predicted proteins are predicted to populate the membranes of intracellular organelles (cytoplasmic, chloroplast, mitochondrial, nuclear), supporting recent study which has showed that the P2X receptors populating the contractile vacuole mediate calcium release and osmoregulation in Dictyostelium discoideum [7,50,51]. We also found that 149 predicted P2X proteins have 2 TM domains, while 25 have only one TM domain, which mostly exist in invertebrates.…”
Section: Resultssupporting
confidence: 83%
“…This result is in accord with the basic function of P2X receptors as ligand-gated ion channels which open to allow ions such as Na+, Ca2+ to pass through the membrane [14]. However, 28 out of 180 predicted proteins are predicted to populate the membranes of intracellular organelles (cytoplasmic, chloroplast, mitochondrial, nuclear), supporting recent study which has showed that the P2X receptors populating the contractile vacuole mediate calcium release and osmoregulation in Dictyostelium discoideum [7,50,51]. We also found that 149 predicted P2X proteins have 2 TM domains, while 25 have only one TM domain, which mostly exist in invertebrates.…”
Section: Resultssupporting
confidence: 83%
“…Activation of ionotropic purinergic receptors triggers Ca 2þ signals in many types of cells [228 -232]. Incidentally, P2X receptors may also serve as intracellular Ca 2þ -release channels, as has been shown in D. discoideum [233], further corroborating an intimate relation between ATP and Ca 2þ from the very early evolution of cellular signalling. The P2X receptors seem to operate in the membranes of other organelles, including mitochondria, lysosomes and nuclei [234], although whether activation of these intracellular receptors is linked to Ca 2þ movements remains to be found.…”
Section: Ca 2þ As a Regulator Of Programmed Cell Deathmentioning
confidence: 90%
“…The PKD2 serves for the perception of fluid flow [108]. In Dictyostelium, Ca 2+ permeable purinoceptors of P2X type, serve as CRCs localised to the contractile vacuole complex [71,109] where they modulate osmoregulation [110]. In plants, InsP 3 Rs and TRPs seem to have disappeared ( [53], this special issue).…”
Section: Other Crcs and Additional Ca 2+ Storesmentioning
confidence: 98%